Narrative Functions and Cultural Adaptation in Torajan Folklore: A Proppian Morphological Analysis of Landorundun: Fungsi Naratif dan Adaptasi Budaya dalam Cerita Rakyat Toraja: Analisis Morfologis Propp terhadap Landorundun - Waruwu, Nito Calvin Zambo; Erfiani, Ni Made Diana; Awololon, Yohanes Octovianus Lesu (Pena : Jurnal Pendidikan Bahasa dan Sastra, 2026)
Landorundun is an oral folklore of the Torajan community in South Sulawesi, Indonesia, and is regarded as one of the region’s most significant traditional narratives. The story recounts the quest of Bendurana, crown prince of the Kingdom of Bone, who journeys to Tana Toraja after discovering a strand of Landorundun’s luminous hair carried to the sea. Guided by supernatural swallows, engaged in londe (traditional poetic exchanges), and aided by a magical mango tree stratagem, Bendurana ultimately secures marriage with Landorundun and establishes a diplomatic alliance between Toraja and Bone. This study examines the narrative structure of Landorundun using Vladimir Propp’s thirty-one narrative functions to identify its morphological pattern and to explore the relationship between universal folktale structure and culturally specific Torajan traditions. Employing a qualitative descriptive approach, the study analyses the written transcription of the folklore through documentation and structural narrative analysis based on Propp’s morphological framework.The findings reveal that the narrative contains twenty-one of Propp’s thirty-one functions, arranged in a sequence consistent with the Proppian model. At the same time, these functions are realised through distinctively Torajan cultural forms, including londe as a test of social competence, the authority of family and noble hierarchy, and the Basse alliance as a symbol of inter-community solidarity. These findings demonstrate both the cross-cultural applicability of Propp’s morphological theory and the importance of local cultural contexts in shaping narrative expression within Indonesian oral tradition.